Impact of health literacy and medication adherence on achieving blood pressure goals among hypertensive patients at the University of Gondar Comprehensive Specialized Referral Hospital, Northwest Ethiopia - Alemante Tafese Beyna; Assefa Kebad Mengesha; Habtamu Semagne Ayele; Firomsen Mamuye Dajane; Abreham Honelgn Mule; Assefa Belay Asrie; Tafere Mulaw Belete; Demis Getachew; Tekletsadik Tekleslassie Alemayehu; Gebresilassie Tadesse; Gebremariam Wulie Geremew; Liknaw Workie Limenh; et al. (PLoS ONE, 2026)
Background This study assessed hypertensive health literacy and its association with achieving blood pressure goals at the University of Gondar Comprehensive Specialized Hospital, Ethiopia. Method A cross-sectional study was conducted with 393 hypertensive patients from September 1 to October 30, 2024, selected through simple random sampling. Data were analyzed using t-tests, one-way ANOVA, and logistic regression, with p < 0.05 considered significant. Result Among the 393 participants, only 40.2% of participant achieved their blood pressure goal. Only 15% and 30.8% had high hypertensive health literacy and adherence levels, respectively. Participants living in an urban area (AOR = 5.1, 95% CI: 2.74–9.17, p < 0.001), with higher education (AOR = 2.7, 95% CI: 1.15–6.75, p < 0.023), living with hypertension for more than 10 years (AOR = 3.4, 95% CI: 1.54–7.58, p < 0.002), using three or more antihypertensive drugs (AOR = 0.3, 95% CI: 0.13–0.95, p < 0.041), adhering to treatment (AOR = 2.7, 95% CI: 1.34–5.55, p < 0.005), and having high hypertension health literacy (AOR = 3.8, 95% CI: 1.36–10.90, p < 0.011) were more likely to achieve blood pressure goal. Variables like residence (p < 0.001), marital status (p < 0.004), educational status (p < 0.013), occupation (p < 0.013), number of antihypertensive medications (p < 0.001), and presence of complication (p < 0.002) showed a significantly mean difference in hypertension health literacy score. There is a significant association between hypertensive health literacy and medication adherence with a p-value of < 0.001. Conclusion Most participants did not achieve their target blood pressure goals. Hypertensive health literacy and medication adherence were significantly associated with blood pressure goals. To improve these outcomes, health policies should focus on creating community-based educational programs that empower patients with a better understanding of their condition and the importance of following their treatment plans. Additionally, increasing access to healthcare resources and support can provide the guidance patients need to manage their hypertension effectively. By strengthening these initiatives, we can help more individuals take control of their health and achieve better blood pressure management.